2020
DOI: 10.1097/wnf.0000000000000391
|View full text |Cite
|
Sign up to set email alerts
|

Real-Word Effectiveness and Safety of Dimethyl Fumarate in a Multiple Sclerosis Portuguese Population

Abstract: Objectives The aim of this study was to evaluate postmarketing dimethyl fumarate (DMF) safety and effectiveness in a real-world population with relapsing-remitting multiple sclerosis (RRMS). Methods This was a retrospective, single-center study with RRMS patients treated with DMF. Demographic, clinical, and imagiological characteristics were analyzed, including annualized relapse rate (ARR), Expanded Disability Status Scale, “No Evidence of Disease Acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…However, a retrospective study by Vollmer et al reported GI disorders in 80.5% of patients [13]. Similarly, a single-center study by Barros et al reported a 42% incidence of GI disorders, with abdominal pain, diarrhea, nausea, and vomiting occurring in 26.7%, 14.8%, 9.6%, and 5.7% of patients, respectively [14,15]. Our study highlights the importance of monitoring adverse events in patients receiving DMF and the potential benefits of a slow dose titration to improve the tolerability of this treatment.…”
Section: Lower Incidence Of Gi Adverse Events Attributed To Slow Dose...mentioning
confidence: 96%
“…However, a retrospective study by Vollmer et al reported GI disorders in 80.5% of patients [13]. Similarly, a single-center study by Barros et al reported a 42% incidence of GI disorders, with abdominal pain, diarrhea, nausea, and vomiting occurring in 26.7%, 14.8%, 9.6%, and 5.7% of patients, respectively [14,15]. Our study highlights the importance of monitoring adverse events in patients receiving DMF and the potential benefits of a slow dose titration to improve the tolerability of this treatment.…”
Section: Lower Incidence Of Gi Adverse Events Attributed To Slow Dose...mentioning
confidence: 96%
“…28 Outside pivotal clinical trials, these findings are further supported by observational studies of patients switching from other first-line therapies to DMF. 122,124,132,[146][147][148][149][150][151] Based on these results, horizontal switching, especially from injectable therapies, is a viable use of DMF.…”
Section: Treatment Switchingmentioning
confidence: 99%
“…Literatür incelendiğinde daha önce başka HMT kullanım oranlarının benzer şekilde %58-%90 arasında olduğu ve YRH'ların 0,5-0,76 arasında bildirildiği görülmüştür. 6,[10][11][12][13][14][15][16] Diğer kohortlar ile büyük oranda benzer olan çalışmamız DMF'nin daha çok ikinci basamakta tercih edildiğini göstermektedir. DMF tedavisi esas olarak birinci basamakta kullanılmak üzere onay almıştır.…”
Section: Bulgularunclassified
“…Ek olarak daha kısa hastalık süresi olan hastalarda daha yüksek etkinlik ve tedavi olduğu da başka çalışmalarda da bildirilmektedir. 10,13 Çalışmamızda da benzer bulgular elde edilmiştir. DMF öncesi EDSS değerlerine bakıldığında hasta kohortumuzda medyan 2.0 EDSS değeri başka kohortlarla benzer olsa da 13,15 , bazılarına göre daha yüksektir.…”
Section: Bulgularunclassified
See 1 more Smart Citation